Delay differential evolutions subjected to nonlocal initial conditions - Burlica, Monica-Dana 1971-; Necula, Mihai; Rosu, Daniela 1968-; Vrabie, I. I. (Ioan I.) 1951- (Monographs and research notes in mathematics, 2016)
Filling a gap in the literature, Delay Differential Evolutions Subjected to Nonlocal Initial Conditions reveals important results on ordinary differential equations (ODEs) and partial differential equations (PDEs). It presents very recent results relating to the existence, boundedness, regularity, and asymptotic behavior of global solutions for differential equations and inclusions, with or without delay, subjected to nonlocal implicit initial conditions.